Soil Sharing and Equipment Operations Through Digitalization of Large-Scale Earthworks - Dongwook Kim (Buildings)
The modern construction industry is undergoing considerable changes driven by increased specialization, technological advancements, and growing complexity. The integration of smart construction technology is rapidly advancing as a solution to address the aging workforce in the sector. However, the uncertainty and risks associated with soil construction on job sites remain, leading to increased costs during project execution. Recently, construction sites have sought to enhance productivity by leveraging building information modeling (BIM) and smart construction devices. The adoption of smart equipment, such as machine control and machine guidance, is on the rise in both structural and earthwork projects, with ongoing efforts to mitigate uncertainties. This study proposes a practical approach to reduce the uncertainty in earthworks by optimizing soil sharing strategies and equipment allocation from the initial design phase. A BIM model was developed as a solid structure and then segmented using Dynamo. This model was utilized to create a construction plan using Primavera P6, while AnyLogic (8.9.2) was employed to assess the suitability of equipment combinations, ultimately demonstrating the cost-saving benefits of the proposed approach. Through repeated simulations, work efficiency was enhanced by approximately 6.2% compared to the original 2D planning approach.